Assessing the mediating effect of customer satisfaction to the relationship of online service quality of cloud kitchen to customers behavioral intention of Co Kitchen brand of Gintong Patatas Enterprise Inc. - de Castro, Lara Angelika B. (Animo Repository, 2022)
The pandemic has prompted several Filipino restaurant chains to establish a strong foundation for their online ordering system, which provides a more extensive selection, greater flexibility, complete transparency, and enhanced security. This study focuses on assessing the mediating effect of Customer Satisfaction on the relationship of Online Service Quality of Cloud Kitchen to Customer Behavioral Intention. The study was conducted on the Co Kitchen brand of Gintong Patatas Enterprises Inc., a Filipino-owned cloud kitchen business. To gather necessary data, the researchers distributed questionnaires to customers by posting them on several social media accounts and cooperating with the company. A total of 161 participants that constitute the sample size. Hypothesis were formulated and tested at .05 significance level. Data were analyzed through Pearson Moment Correlation, Linear Regression and Barron and Kenny’s Mediation Analysis Model. The result reveals a significant relationship between Online Service Quality and its dimensions (Perceived Control, Service Convenience, Customer Service, and Service Fulfillment) to Customer satisfaction with a p-value of < 0.05. Through linear regression analysis, the result shows that Perceived Control, Service Convenience, Customer Service, and Service Fulfillment have a significant effect on Customer Satisfaction, given that they all have a p-value < 0.05. Meanwhile, Barron and Kenny’s mediation model analysis showed that Customer Satisfaction has a full mediating effect on the relationship between Online Service Quality Dimensions and Customer Behavioral Intention. With this, the researchers recommend that the Co Kitchen brand of Gintong Patatas Enterprises Inc. should enhance the Online Service Quality Dimensions to acquire and attract more customers to purchase their products. This could help the brand obtain long-term customers, which would then establish brand loyalty. Lastly, it would increase the number of customers willing to purchase their products repetitively.